Correlation between visually estimated and calculation of blood loss during delivery in nulliparous women - Vizarreta Cherre, Lourdes (2015)
Objectives: To correlate the visual estimated blood loss (vEBL) with the calculated estimated blood loss (cEBL) during delivery in nulliparous women. Design: Correlation retrospective study. Setting: Hospital Nacional Cayetano Heredia, Lima, Peru. Study material: Medical records. Methods: We reviewed 225 medical records of at term nulliparous patients’ vaginal deliveries attended between July and December 2009. Main outcome measures: Correlation between visually estimated and calculated blood loss. Results: Mean vEBL and cEBL were respectively 285.70 ± 82.77 mL and 534.75 ± 367.58 mL. Hematocrit descended 3.8%. There was a significant underestimation between vEBL regarding cEBL in episiotomies (p=0.0000) and 3th and 4th degrees lacerations. The Spearman correlation coefficient for vEBL and cEBL was 0.06 (p=0.31). Conclusions: No  correlation was found between vEBL and cEBL. Visual estimation of intrapartum bleeding is inaccurate to calculate blood loss volumes. Effective alternatives methods are required that includes an estimated  maternal blood volume formula and changes in hematocrit.